Analysis of Deixis Types in Joko Widodo's Speech: A Pragmatic Linguistics Study - Anggun Purnomo Arbi (International Journal of Integrated Science and Technology, 2023)
The purpose of this study, "Analysis of Deixis Types in Joko Widodo's Speech: A Pragmatic Linguistics Study," is to identify and classify the many types of deixis used in Joko Widodo's speeches. Personal deixis, temporal deixis, spatial deixis, discourse deixis, and social deixis are five different categories of deixis that are identified. The study uses a pragmatic linguistic framework and a descriptive analytic methodology. The information for the study was taken from transcripts of speech given by Joko Widodo performed at the Sentul International Convention Centre in Bogor, West Java.The analysis demonstrates that the use of deixis in Joko Widodo's speeches contributes significantly to rhetorical efficacy, political discourse building, and communication techniques. The study's conclusions can be applied to language instruction, communication training, and giving public speakers advice on how to use deixis effectively. Future research directions can look at differences in deixis usage in various circumstances or comparison analysis with other political speeches.